Competence for transcellular infection in the root cortex involves a post-replicative, cell-cycle exit decision in Medicago truncatula - Morgane Batzenschlager; Beatrice Lace; Ning Zhang; Chao Su; Anna Boiger; Sabrina Egli; Pascal Krohn; Jule Salfeld; Franck Anicet Ditengou; Thomas Laux; Thomas Ott (eLife)
During root nodule symbiosis (RNS), cell-division activity is reinitiated and sustained in the root cortex to create a hospitable cellular niche. Such a temporary and spatially confined site is required to render host cells compatible with the intracellular progression of rhizobia. Although it has been suggested that early infection events might involve a pre-mitotic cell-cycle arrest, this process has not been dissected with cellular resolution. Here, we show that a dual-color Medicago histone reporter robustly identifies cells with different mitotic or endoreduplication activities in the root cortex. By imaging deep root tissues, we found that a confined trajectory of cortical cells that are transcellularly passed by infection threads is in a stage of the cell cycle that is distinct from directly adjacent cells. Distinctive features of infected cells include nuclear widening and large-scale chromatin rearrangements consistent with a cell-cycle exit prior to differentiation. Using a combination of fluorescent reporters demarcating cell-cycle phase progression, we confirmed that a reduced proliferation potential and modulating the G2/M transition, a process possibly controlled by the NF-YA1 transcription factor, mark the success of rhizobial delivery to nodule cells.